The Influence of Principals' Transformative Leadership Styles on Organizational Culture and Teacher Performance - Sopian Hadi, Heri; Zamroni (ARMADA : Jurnal Penelitian Multidisiplin, 2025)
This study aims to analyse the implementation of restorative justice principles in resolving juvenile offences within the school environment, focusing on a case study at three public junior high schools, specifically SMPN 1 Praya Timur in Central Lombok Regency. The background of this research is based on the increasing number of legal violations and acts of violence among students, which, if addressed through repressive measures, may result in long-term negative impacts on child development. The data for this study were obtained from observations and interviews conducted with teachers, staff, and students. The data analysis techniques applied include data reduction, data presentation, conclusion drawing, and triangulation. Restorative justice places perpetrators, victims, and the community in an equal dialogue space to resolve conflicts, restore conditions to their original state, and prevent repeated violations. In the school context, restorative justice has begun to be implemented through approaches such as peer mediation, family conferences, and dialogues between perpetrators and victims mediated by counselling teachers or school principals. Some schools in Central Lombok, particularly SMPN 1 Praya Timur, have attempted to adopt these principles in handling student-related violations. However, the implementation of restorative justice in these schools has not yet been systematically or academically documented. Therefore, the application of restorative justice in addressing cases of juvenile delinquency such as fighting, theft, or violence needs to be implemented more effectively, particularly in schools, and requires further in-depth study.